171k views
2 votes
Use the Distributive Property to solve the equation.

6​(x−​6)+8=8x−6
The solution of the equation is

2 Answers

7 votes


6(x-6)+8=8x-6\\6x-36+8=8x-6\\2x=-22\\x=-11

User Mr Moose
by
5.1k points
1 vote

Hey there!

6(x - 6) + 8 = 8x - 6

6(x) + 6(-6) + 8 = 8x - 6

6x - 36 + 8 = 8x - 6

6x - 28 = 8x - 6

SUBTRACT 8x to BOTH SIDES

6x - 28 - 6x = 8x - 6 - 8x

WORK IT OUT/SIMPLIFY IT!

NEW EQUATION: -2x - 28 = -6

ADD 28 to BOTH SIDES

-2x - 28 + 28 = -6 + 28

CANCEL out: -28 + 28 because it gives you 0

KEEP: -6 + 28 because it help you solve for the x-value

NEW EQUATION: -2x = -6 + 28

SIMPLIFY IT!

-2x = 22

DIVIDE -2 to BOTH SIDES

-2x/-2 = 22/-2

CANCEL out: -2/-2 because it gives you 1

KEEP: 22/-2 because it help you solve for the x-value

NEW EQUATION: x = 22/-2

SIMPLIFY IT!

x = -11

Therefore, your answer is: x = -11

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Xavier Noria
by
5.6k points